Facing the Heat: Thermoregulation and Behaviour of Lowland Species of a Cold-Dwelling Butterfly Genus, Erebia - Kleckova, Irena; Klecka, Jan (PloS one, 2016)
Understanding the potential of animals to immediately respond to changing temperatures is imperative for predicting the effects of climate change on biodiversity. Ectothermic animals, such as insects, use behavioural thermoregulation to keep their body temperature within suitable limits. It may be particularly important at warm margins of species occurrence, where populations are sensitive to increasing air temperatures. In the field, we studied thermal requirements and behavioural thermoregulation in low-altitude populations of the Satyrinae butterflies Erebia aethiops, E. euryale and E. medusa. We compared the relationship of individual body temperature with air and microhabitat temperatures for the low-altitude Erebia species to our data on seven mountain species, including a high-altitude population of E. euryale, studied in the Alps. We found that the grassland butterfly E. medusa was well adapted to the warm lowland climate and it was active under the highest air temperatures and kept the highest body temperature of all species. Contrarily, the woodland species, E. aethiops and a low-altitude population of E. euryale, kept lower body temperatures and did not search for warm microclimates as much as other species. Furthermore, temperature-dependence of daily activities also differed between the three low-altitude and the mountain species. Lastly, the different responses to ambient temperature between the low- and high-altitude populations of E. euryale suggest possible local adaptations to different climates. We highlight the importance of habitat heterogeneity for long-term species survival, because it is expected to buffer climate change consequences by providing a variety of microclimates, which can be actively explored by adults. Alpine species can take advantage of warm microclimates, while low-altitude grassland species may retreat to colder microhabitats to escape heat, if needed. However, we conclude that lowland populations of woodland species may be more severely threatened by climate warming because of the unavailability of relatively colder microclimates.
Keywords: Body Temperature Regulation; druhová specificita; Animals; nadmořská výška; Behavior, Animal; Cold Temperature; Hot Temperature; termoregulace; chování zvířat; zvířata; Altitude; nízká teplota; Butterflies; Climate; Species Specificity; vysoká teplota; podnebí; motýli